Effect of processed spent bleaching earth and kenaf fibre on compressive strength and drying shrinkage of foamed concrete - Mohammad Amin, Mahmood (2019)
Pozzolanic material produced by combustion of the waste from natural or artificial material. In this study, Processed Spent Bleaching Earth (PSBE) is a by-product from the degumming and bleaching of crude palm oil (CPO) from physically refined palm oil is commonly disposed of at landfills at a high cost. In this present study, PSBE used as partial cement replacement to Ordinary Portland Cement (OPC). These are three mixture has been prepared, namely foamed concrete (FC), foamed concrete with 30% PSBE (PFC) and foamed concrete with 30% PSBE and 0.5% kenaf fiber (PKC). All specimens were prepared to investigate the compressive strength, shrinkage, weight loss and carbonation depth. The result for compressive strength, the mixture contains 30% PSBE as partial cement replacement produced the highest compressive stress compared to FC and PKC. Other than that, the mixture that presence kenaf fiber, which is PKC, shows the lower shrinkage compared to PFC and FC. Besides that, the result for shrinkage influence for the result of the percentage of weight loss, which means the PKC have a lower percentage of weight loss compared to PFC and FC. Meanwhile, FC produced the highest value for the carbonation depth of foamed concrete compared to PFC and PKC. The study implies PSBE as partial replacement is useful and beneficial, especially for the production for foamed concrete.